Edukasi Manajemen Airway (Teknik Haemlich Manouver) Pada Masyarakat Di Kota Jambi - pairi, agus; Imran, Suryadi; sunanto, sunanto (Jurnal Abdimas Multidisiplin, 2024)
Airway Management is the management of patients with airway disorders that result in a person experiencing respiratory arrest, and if not treated immediately it will result in the death of the victim, this condition is usually caused by partial airway obstruction or total airway obstruction, are Many cases occur in the community due to lack of knowledge about first aid management for digestive cases that cause airway obstruction, for this reason, it is necessary to provide education and demonstration of first aid methods for victims who experience airway obstruction, thereby reducing the risk of death due to the victim not receiving oxygen. . The implementation of this community service was carried out in sub-districts throughout Jambi City with the aim of increasing community knowledge in providing first aid to victims of gnat cases which often occur in the community. The participants of this education were 60 people which were divided into 2 morning and afternoon sessions. This activity helped with the Jambi City Health Service, and the District Office in Jambi City